KARAKTERISTIK KONTAINER TERHADAP KEBERADAAN JENTIK AEDES AEGYPTI DI SEKOLAH DASAR - BUDIYANTO, ANIF (Badan Penelitian dan Pengembangan Daerah Provinsi Sumatera Selatan, 2012)
Background: Dengue vector breeding places are containers inside and outside the school building. Presence or absence of Ae aegypti mosquito larvae in a container is affected by the type, location, color, material, condition and volume of container lid. The purpose of this study was to determine the condition of container that affect the presence of Ae aegypti mosquito larvae.Methods: A cross sectional study design. Data was collected by conducting surveys of mosquito larva in primary schools in the district. Larvae survey with single method. Results: Most schools (54%) found larvae, and larvae found in most (91%) is Ae aegypti. There was a significant difference, between dark and light color differences in the presence of mosquito larvae (Pv = 0.017, CI95% = 1.2 to 2.9). There was no significant difference between different types of containers, the location of containers, containers color, material containers, the container lid and the volume of water in a container in the presence of larvae. Conclusion: There is significant difference, between the difference in container color (light and dark) in the presence of Ae aegypti mosquito larvae. Therefore advised to seek regular cleaning of the container, so it does not arise dirt / moss which causes the impression of being a dark container.